Spectrophotometric Determination of Factor Xa Generation in Factor IX Concentrates - Pepper, D. S; Banhegyi, D; Howie, Ann (Thrombosis and Haemostasis, 1977)
Previous work from this department, concerned with testing the potential thrombogenicity of therapeutic factor IX concentrates, demonstrated that following recalcification of factor IX concentrates thrombin was generated within 3-30 minutes of incubation (Sas et al. 1975). The test developed (known as the TGt 50 test) is a two-stage assay and was thus found to be time consuming, tedious and tended to become inaccurate with long incubation periods and a large number of samples. A semiautomatic version of the test is reported in which the synthetic peptide Bz-ILE-GLU-GLY-ARG-pNA (S-2222) is added to recalcified, diluted factor IX concentrate in the micro-cuvette of a multiple sample recording spectrophotometer. Information can be obtained on (a) the amount of Xa (if any) present prior to recalcification (b) the initial amount of Xa formed and (c) the time taken to activate all factor X to Xa. Direct graphical interpretation shows a number of qualitative differences between commercial preparations, but by either of the criteria (b) or (c) above, it is possible to place the different products into “activated” and “non activated” groups such that both the Xa generation times and TGt 50 tests identify the same two groups of products. This agreement also indicates that the TGt 50 test is independent of the intrinsic factor V levels in the various concentrates.